Spatial Planning for Coastal Area Based on Tsunami Hazard in Bulukumba Regency - Sakti, Harry Hardian; Radhinal, Yan; Ahmad, Despry Nur Annisa; Aldiansyah, Farhan (Universitas Muhammadiyah Makassar, 2025)
ABSTRACT: The record of disasters in coastal areas that have occurred in Bulukumba Regency is the tsunami event due to an earthquake on December 29, 1820. The epicenter in the Flores Sea and the death toll in Bulukumba Regency at that time reached around 500 people. This event needs to be an early preparedness because tectonic disasters have the potential for a period of repetition. The purpose of this study is to analyze the tsunami hazard level and formulate coastal spatial planning policies based on the potential tsunami hazard of Bulukumba Regency. The methods used are statistical, descriptive qualitative, and spatial analysis approaches. The parameters used in determining the tsunami hazard level are earthquake hazard level, land elevation, slope slope, distance from rivers, and morphology. The results show that the coastal area is predominantly classified into low- and medium-hazard categories. Low-hazard zones occupy the largest spatial extent (notably Gantarang: 16,659.42 ha; Ujung Loe: 14,535.05 ha), while medium-hazard zones are more spatially limited but concentrated in critical locations (e.g., Bonto Bahari: 732.35 ha; Kajang: 423.06 ha; Herlang: 365.75 ha). Under a worst-case seismic scenario (7.0–7.5 Mw), the potentially affected area is estimated at 19,784 ha (25.85% of the coastal land area), with an exposure of >67,000 buildings, predominantly in Ujung Bulu (42,213 buildings). These findings have direct implications for the Regional Spatial Plan (RTRW). We recommend (1) restricting new development in identified medium-/high-exposure coastal segments, (2) designating Temporary Evacuation Sites (TES) on topographically safe locations (slope > 2%), and (3) integrating evacuation routes with the existing urban road network to ensure rapid accessibility. By providing quantitative hazard maps and concrete policy recommendations, this study fills a critical gap between tsunami hazard assessment and coastal spatial planning in Bulukumba, offering an evidence base for resilience-building and further risk-focused research.